Psychometric properties of two mental health screening tools in southeast Liberia: The Liberian Distress Screener and Patient Health Questionnaire. (August 2022) - Fabian, Katrin E.; Fannoh, Josiah; Washington, George G.; Geninyan Weetol, Wilfred B.; Nyachienga, Bethuel; Cyrus, Garmai; Hallowanger, Joyce N.; Beste, Jason; Augusto, Orvalho; Wagenaar, Bradley H.
Evidence suggests that locally developed and/or adapted screening tools for mental ill-health can have higher validity than directly translated tools developed in other settings. We administered the locally developed Liberian Distress Screener (LDS) and the Liberian-adapted Patient Health Questionnaire-9 (PHQ-9L) to a random sample of 142 outpatients at a regional hospital in Maryland County, Liberia. In the LDS, seven items demonstrated poor model fit and were excluded, resulting in an 11-item screener (LDS-11). Exploratory factor analysis of the 11-item screener (LDS-11) showed a single latent variable construct with significant factor loadings. Cronbach's alpha revealed good internal consistency (α = 0.81). Rasch analyses showed that "brain hot" and "heart fall down" were the most difficult idioms of distress to endorse while "things playing on the mind" was the easiest. All LDS-11 elements were associated with elevated function impairment, with "things playing on the mind, " "worry too much, " "head is hurting, " and "heart cut/beat fast" achieving statistical significance. One item in the PHQ-9L demonstrated poor model fit and was excluded from psychometric analyses. The resultant eight-item PHQ demonstrated internal consistency (α = 0.76) and Rasch analysis revealed that "moving/talking too slowly/fast" was the most difficult item to endorse, while "not happy when doing things" was the easiest. Twelve items were significantly associated with functional impairment. Exploratory analyses reveal items that demonstrate ease and appropriateness of use for assessing mental distress in this population. Implementation research is needed to incorporate idioms of distress and screeners into Liberia's mental healthcare system.